Is decreased diameter of renal pelvis in prone position an indicator of successful pyeloplasty? - Gyanendra Sharma; Anshu Sharma; Vivian Yee-Fong Leung; Winnie Chiu-Wing Chu (Indian Journal of Radiology and Imaging, 2016)
Objective: To evaluate patients who had undergone pyeloplasty for pelviureteric junction obstruction, by measuring the anteroposterior diameter (APD) of the renal pelvis in supine and prone positions, and determine whether a decrease in APD in prone position can exclude obstruction in dilated renal system. Materials and Methods: From January 2012 to December 2013, patients who had undergone pyeloplasty were evaluated by ultrasound in two centers. The difference of APD of the renal pelvis in supine and prone positions was obtained. Correlation was made with the pre- and post-pyeloplasty renal function by radionuclide renogram. Results: There were 42 patients (31 males, 11 females; age range 5 months to 18 years). Residual hydronephrosis was detected in 41 patients of whom 35 patients (85%) showed decrease in APD by >10% in prone position. These patients and the one without hydronephrosis showed either no deterioration or improvement in renal function. Six patients (15%) showed either no change or increase in APD in prone position. Three patients (7.5%) were confirmed to have decrease in renal function indicating obstruction. Three patients (7.5%) showed no deterioration of renal function, but sluggish drainage on radionuclide renogram. Conclusion: Demonstration of decreased APD of renal pelvis in prone position by ultrasound is useful to differentiate obstructed from non-obstructed dilated renal system, and it correctly identified 85% candidates with successful pyeloplasty. In patients with no decrease or increase in APD at prone position, further follow-up is recommended to rule out obstruction.